Breeding biology of the Black Swan Cygnus atratus in southeast Queensland, Australia - Coleman, Jonathan (Wildfowl, 2014)
The breeding biology of Black Swans Cygnus atratus ringed on the Gold Coast of southeast Queensland, Australia, was studied from 2007–2012. Numbers breeding ranged from 13–23 pairs per annum and included between 23–39 recorded breeding attempts by marked birds each year (total = 185 attempts over the 6-year study), of which 36% of all breeding attempts were unsuccessful. In years of high rainfall, total numbers of breeding pairs and breeding attempts were higher, as was the percentage of breeding failures. Of 119 instances of pairs recorded breeding, 63% bred once per year, 26% bred twice, 31, 6% three times, 3% four times and 3% bred five times in one year. Over half of all follow-on breeding attempts were preceded by a successful breeding attempt; in four cases, three broods of cygnets were hatched in a single year. On average, birds nesting 3–5 times per year had no better productivity per breeding attempt than those nesting only once or twice, although they did produce more cygnets each year. Birds were first recorded pairing at 2–4 years of age, and first recorded breeding at 2–5 years (most at three years old). The mean number of cygnets hatched per breeding attempt varied between 1.61–2.61 cygnets for each year of the study and the mean number of cygnets reared to fledging varied from 0.96–2.20 cygnets per breeding attempt. Cygnets hatched in every month of the year except for November, with the highest numbers hatched in March–April and August–September. Results from this study of Black Swans breeding territorially are compared with earlier observations of Black Swans nesting colonially in Australia and New Zealand.